The Influence of Leadership and Work Motivation on Employee Performance at KSPPS BMT Peta, Kediri Sub-branch - Muhammad Sujoko; Sudjiono Sudjiono; Djunaidi Djunaidi; Nonni Yap (Universitas Ichsan Sidenreng Rappang, 2026)
This research aim to know the influence of leadership Policy and motivate the job to employee’s performance at KSPPS BMT PETA Cabang Pembantu Kediri. Research uses the quantitative method that is a method elaborating about a becoming object research. Population in this research is all employees at KSPPS BMT PETA Cabang Pembantu Kediri amounting to 112 employees. While sample as much 53 people/responder. Method of data collecting use the perception (observation), equates method (questioner), and documentation method. While method analyze the data with the test of validity and reliabilities, test the classic assumption, test the doubled linear regresi, and test the significant by partial (statistical test t, significance test in concern/simultan (statistical test f, and coefficient determinacy. From this research result is inferential that: (1) leadership Policy have positive correlation to but do not significant to employees performance at KSPPS BMT PETA Cabang Pembantu Kediri. This Matter is show with the value of equal to statistical test result of Ttest (test the partial) showing value do not significance attitude of equal to 0,159 > 0,05. (2) Motivation work to have an effect on positive and significant to employee’s performance at KSPPS BMT PETA Cabang Pembantu Kediri with the result of result of statistical test of Ttest (test the partial) showing value of significance facility of equal to 0,019 < 0,05. This matter is indication that motivation work very having an effect on to somebody behavior in working, so that motivate the job have to always improved for the stimulus of the spirit of employees job in reaching company target. (3) There are influence by simultan between leadership policy and motivate the job to employees performance at KSPPS BMT PETA Cabang Pembantu Kediri. This Matter is visible from result test the Ttest (test the partial) showing value of leadership policy of equal to 0,159 less than assess the significance motivate the job of equal to 0,019, while the rest influenced